Circular Economy and Industry 4.0 Technology Integration Framework for the Oil Palm Industry - Chun Hsion Lim (AIDIC Servizi S.r.l., 2021)
Palm oil is a sustainable resource with high potential to substitute fossil fuels as the raw material for cleaner energy and chemical production. The oil palm industry is highly dependent on manual labour operation, especially its upstream operation, i.e., plantation. With the rapid development of process automation, robotic, internet-of-things (IoT) and big data analysis, adaptation of Industry Revolution 4.0 (IR4) has proven to be a great strategy to improve process efficiency. Each of the IR4 component/technology may be integrated for its specific feature, such as robotic drone with artificial intelligence data analysis to process captured image. Such technology could be further upgraded with more IR4 technologies integration. This paper proposes a novel circular economy framework to evaluate the potential of implementing IR4 technologies in the oil palm industry. Upon identify viable IR4 technologies for the industry, the cost of investment between the new and existing technologies were compared. Return on investment (ROI) and capital investment were used as the selection criteria to assist the palm oil stakeholders in the decision-making process. Graphical pinch analysis tool is adapted to identify an optimum solution. A case study involving oil palm plantation in Malaysia is analysed. An investment on spray drone for pesticide application was proven to have higher ROI, as compared to the spray tractor and existing practise of using knapsack sprayer. While another drone application for tree health and fruit monitoring has a positive ROI too, it is not possible to invest in both technologies due to budget limitation. Based on circular economy concept, investment into the spray drone and modified drone with smart spectrometer for tree health and fruit monitoring are better strategies to minimise IR4 investment.